Servant Leadership Improves the Knowledge Sharing Behavior of Employees in Organization: A Case of Higher Education Sector in Pakistan - Hina Amin; Farhan Ahmed; Riaz Hussain Soomro (Faculty of Economic and Business, 2019)
The purpose of this paper is to investigate the role of servant leadership in organizations in Karachi and to investigate the level of knowledge sharing (KS) behavior among employees. The study based on quantitative design and the primary data has collected from the higher education sector through a survey questionnaire. Furthermore, multiple regressions have used for model testing. The findings of the study-enlightened benefits of knowledge sharing behavior that can be prevailed through a servant leadership model and encourage employees' participation. Four traits of servant leadership that are altruistic calling, emotional healing, and organizational stewardship have a positive impact on knowledge sharing behavior of employees. The findings of the study will be beneficial for the employees of the organization to understand the importance of servant leadership and its application in enterprises.JEL Classification: J59, M19, M54